Strategi Pengawasan Kepala Desa dalam Implementasi Sistem Keuangan Desa (Siskeudes) di Desa Kwang Rundun Kecamatan Jerowaru: Village Head Supervision Strategy in the Implementation of the Village Financial System (SISKEUDES) in Kwang Rundun Village, Jerowaru District - Muhamad Zaril Gapari; Lalu Moh. Fahri; Ahmad Marsawan Khaliq; Alwi Sahri Ramdhani; Ahmad Gozali Aji (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2026)
The Village Financial System (SISKEUDES) is a crucial instrument for achieving transparent and accountable village financial management. This research is motivated by the need to strengthen the village head's oversight function regarding the implementation of SISKEUDES as a form of good village governance. The research problem formulation includes the supervisory strategies implemented by the village head and the factors influencing them. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman. The results indicate that the village head's oversight strategy is integrative through a participatory approach, direct involvement, public transparency, and internal coordination. Supporting and inhibiting factors include human resource capacity, infrastructure, the role of the Village Consultative Body (BPD), and the level of community participation. In conclusion, the effectiveness of oversight is highly dependent on the synergy between village leadership, apparatus capacity, and institutional social support.